Preparation method of metal cluster-based infrared electroluminescent device
By constructing a host-guest material system of metal cluster Au16Cu6 and host materials mCP and PO-T2T, the problem of low luminous efficiency of metal cluster films in infrared emission applications is solved, and infrared LEDs with high brightness and high external quantum yields are achieved, which improves the spectral stability and color purity of the device.
Patent Information
- Application Number
- CN202411462937.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-19
- Publication Date
- 2025-02-28
AI Technical Summary
While ensuring the good morphology of the metal cluster film, it is difficult to ensure its luminous efficiency, especially in the application of the near-infrared emission band, it is difficult to design high-performance metal cluster diodes in the prior art.
A host-guest material system constructed by metal cluster Au16Cu6 and host materials mCP and PO-T2T is used to form a uniform luminescent layer through spin coating operation, and an electron transport layer and electrode layer are deposited by thermal evaporation to prepare a metal cluster electroluminescent device based on the host-guest material system.
The high brightness and high external quantum yield of infrared LEDs have been achieved, and the spectral stability and color purity of the device have also been significantly improved, solving the problem of low luminescence efficiency of metal cluster films in infrared emission applications.
Smart Images

Figure CN119546135A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electronic device manufacturing, and in particular relates to a method for preparing a metal cluster-based infrared electroluminescent device. Background Art
[0002] Metal clusters have excellent optoelectronic properties. Their low toxicity, high photoluminescence quantum yield, and simple synthesis conditions make them candidate materials for the next generation of light-emitting diodes. In recent years, metal cluster light-emitting diodes (LEDs) in the visible wavelength range have developed rapidly, and their peak efficiency is comparable to that of some traditional organic light-emitting diodes.
[0003] However, metal cluster diodes (LEDs) in the near-infrared emission band for use in detection, diagnosis, treatment, night vision imaging and other fields have never been designed. The main reasons are: 1) There are few existing high-performance infrared-emitting metal clusters, making it difficult to ensure the excellent optical properties of the emitter; 2) The thermally induced phase separation characteristics of metal clusters make it difficult to adapt to the evaporation processing technology, and their unique nanosize makes it difficult to form a uniform and stable thin film structure by spin coating.
[0004] Therefore, ensuring the good morphology of the cluster film while ensuring its luminescence efficiency has become a technical problem that needs to be urgently solved in this field. The solution to this problem will further expand the optoelectronic applications of metal clusters. Summary of the invention
[0005] The invention provides a method for preparing a metal cluster-based infrared electroluminescent device, so as to solve the problem that the luminous efficiency of the cluster film cannot be well guaranteed while the morphology of the cluster film is good.
[0006] The technical solution adopted by the present invention comprises the following steps: Step 1: Take 5 ml of toluene containing Me2SAuCl, add 4-tBuPhC≡CH and Et3N, and stir for 4-6 minutes; Step 2: Add Cu(MeCN)4BF4, then quickly add 1 ml of freshly prepared BH3·tBuNH2 in ethanol, and stir the reaction mixture in the dark at 20°C for 3.5-4.5 hours; Step 3: The solvent obtained in step 2 was rotary evaporated to obtain a solid, and the solid was dissolved in 2.0 ml of a 1:1 mixture of chromatographic grade dichloromethane and toluene, and centrifuged for 2-4 minutes; Step 4: Filter the precipitate in step 3 and collect the filtrate, let it stand in a fume hood and use n-hexane diffusion crystallization to obtain dark red block crystals of Au after 96 hours. 16 Cu6; Step 5: dissolving the crystals obtained in step 4 in chromatographically pure dichloromethane and adding powdered host material mCP and PO-T2T to the solution, stirring vigorously for 4 to 6 minutes to obtain a uniformly distributed host-guest mixed solution; Step 6: Spin-coat the host-guest mixed solution in step 5 onto the ITO glass substrate on which PEDOT:PSS has been spin-coated to serve as a light-emitting layer; Step 7: The product obtained in step 6 is finally transferred into a vacuum chamber, and TPBi, LiF and Al layers are sequentially deposited by thermal evaporation, wherein the TPBi layer serves as an electron transport layer and a hole blocking layer, and the LiF and Al layers serve as top electrodes; thus, a metal cluster electroluminescent device based on a host-guest material system is obtained.
[0007] In the step 1 of the present invention, the mass of Me2SAuCl is 29.5 mg, and the volumes of the solution of 4-tBuPhC≡CH and Et3N are 18 μL and 40 μL, respectively.
[0008] The masses of Cu(MeCN)4BF4 and BH3·tBuNH2 described in step 2 of the present invention are 12.6 mg and 1.7 mg respectively.
[0009] In step 3 of the present invention, the centrifugal speed is 11000-13000 r / min.
[0010] In step 5 of the present invention, the Au 16 The masses of Cu6 and the main materials mCP and PO-T2T are 5.0 mg, 1.0 mg and 1.0 mg respectively.
[0011] In step 6 of the present invention, the ITO conductive glass is first cleaned with soap, deionized water, ethanol, chloroform, acetone and isopropanol in sequence, and then treated with ultraviolet ozone; the PEDOT: PSS solution is spin-coated on the treated ITO glass through a filter head, and then annealing is performed to obtain a hole injection layer; and then the substrate is transferred to a glove box filled with N2 gas.
[0012] The annealing treatment of PeDOT: PSS in the present invention is specifically annealing at a temperature of 170° C. for 30 minutes.
[0013] The rotation speed of the spin-coated PeDOT:PSS of the present invention is 1900-2100 r / min.
[0014] In step 6 of the present invention, the host-guest mixed solution is spin-coated on the PeDOT: PSS layer at a rotation speed of 1900-2100 r / min.
[0015] In step 7 of the present invention, the evaporation rates of TPBi and LiF are 0.1 nm / s, and the evaporation rate of Al is 1 nm / s.
[0016] The advantage of the present invention is that the metal cluster Au is used 16 The host-guest material system constructed by Cu6 and the host material mCP, PO-T2T is used to prepare metal cluster-based infrared LEDs. The introduction of the host material ensures the uniformity of the metal cluster film. Furthermore, the host-guest material system is used as the emission layer to prepare an infrared metal nanocluster-based LED with an electroluminescence (EL) wavelength of 678nm. The device has a wavelength of 224 cd / m 2 The device has a high brightness and a high external quantum yield (EQE) of 0.176%. At the same time, the balanced carrier transport environment in the device greatly improves the spectral stability of the device. The preparation method of the metal cluster-based infrared electroluminescent device provided by the present invention is simple to operate, takes less time, consumes less energy, has simple process requirements, and the prepared metal cluster film has low surface roughness, high external quantum efficiency, high color purity, and good device stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The crystal synthesized by the present invention has the characteristic absorption peak position and emission peak position diagram of metal nanoclusters; Figure 2 is a transient photoluminescence spectrum diagram of the present invention; Figure 3 This is a roughness comparison diagram of the metal cluster film optimized by the host-guest material system and the metal cluster film not optimized in the present invention; Figure 4 is the semiconductor energy level diagram of the measured cluster emitter; Figure 5 It is the electroluminescence spectra of the unoptimized metal clusters and the metal nanoclusters optimized by the host-guest material system; Figure 6 is the brightness graph of the optimized LED; Figure 7 This is the peak external quantum efficiency diagram of the optimized LED. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Example 1
[0019] The following steps are involved: 1) Take 5 ml toluene containing Me2SAuCl (29.5 mg, 0.1 mmol), add 4-tBuPhC≡CH (18 μL, 0.1 mmol) and Et3N (40 μL), and stir for 4 minutes; 2) Add Cu(MeCN)4BF4 (12.6 mg, 0.04 mmol), and then quickly add 1 ml of freshly prepared BH3·tBuNH2 ethanol solution (1.7 mg). The reaction mixture is stirred in the dark at 20 °C for 3.5 hours. 3) The solvent obtained in 2) was rotary evaporated to obtain a solid, and the solid was dissolved in 2.0 ml of a 1:1 mixture of chromatographic grade dichloromethane and toluene, and centrifuged at 13000 r / min for 2 minutes; 4) Filter the precipitate in 3) and collect the filtrate, let it stand in a fume hood and use n-hexane diffusion crystallization to obtain dark red block crystals of Au after 96 hours. 16 Cu6; 5) dissolving the crystals obtained in 4) in chromatographically pure dichloromethane and adding powdered host material mCP and PO-T2T to the solution, stirring vigorously for 4 minutes to obtain a uniformly distributed host-guest mixed solution; 6) Spin coating the host-guest mixed solution in 5) onto the ITO glass substrate on which PEDOT:PSS has been spin-coated at a speed of 1900 rpm / s; comprising: First, the ITO conductive glass was cleaned with soap, deionized water, ethanol, chloroform, acetone and isopropanol in turn, and then treated with UV ozone. PEDOT: PSS solution (Baytron PVP Al 4083) was spin-coated on the treated ITO glass through a filter head at a speed of 1900 r / min, and then annealed at 170°C for 30 minutes to obtain a hole injection layer. The substrate was then transferred to a glove box filled with N2 gas. 7) The product obtained in 6) is finally transferred into a vacuum chamber, and TPBi, LiF and Al layers are sequentially deposited by thermal evaporation, wherein the TPBi layer serves as an electron transport layer and a hole blocking layer, and the LiF and Al layers serve as top electrodes; thus, a metal cluster electroluminescent device based on a host-guest material system is obtained, wherein the evaporation rates of TPBi and LiF are 0.1 nm / s, and the evaporation rate of Al is 1 nm / s. Example 2
[0020] The following steps are involved: 1) Take 5 ml toluene containing Me2SAuCl (29.5 mg, 0.1 mmol), add 4-tBuPhC≡CH (18 μL, 0.1 mmol) and Et3N (40 μL), and stir for 6 minutes; 2) Add Cu(MeCN)4BF4 (12.6 mg, 0.04 mmol), and then quickly add 1 ml of freshly prepared BH3·tBuNH2 ethanol solution (1.7 mg). The reaction mixture is stirred in the dark at 20 °C for 4.5 hours. 3) The solvent obtained in 2) was rotary evaporated to obtain a solid, and the solid was dissolved in 2.0 ml of a 1:1 mixture of chromatographic grade dichloromethane and toluene, and centrifuged at 11000 r / min for 4 minutes; 4) Filter the precipitate in 3) and collect the filtrate, let it stand in a fume hood and use n-hexane diffusion crystallization to obtain dark red block crystals of Au after 96 hours. 16 Cu6; 5) dissolving the crystals obtained in 4) in chromatographically pure dichloromethane and adding powdered host material mCP and PO-T2T to the solution, stirring vigorously for 6 minutes to obtain a uniformly distributed host-guest mixed solution; 6) Spin coating the host-guest mixed solution in 5) onto the ITO glass substrate on which PEDOT:PSS has been spin-coated at a speed of 2100 rpm / s; comprising: First, the ITO conductive glass was cleaned with soap, deionized water, ethanol, chloroform, acetone and isopropanol in turn, and then treated with UV ozone. PEDOT: PSS solution (Baytron PVP Al 4083) was spin-coated on the treated ITO glass through a filter head at a speed of 2100 r / min, and then annealed at 170°C for 30 minutes to obtain a hole injection layer. The substrate was then transferred to a glove box filled with N2 gas. 7) The product obtained in 6) is finally transferred into a vacuum chamber, and TPBi, LiF and Al layers are sequentially deposited by thermal evaporation, wherein the TPBi layer serves as an electron transport layer and a hole blocking layer, and the LiF and Al layers serve as top electrodes; thus, a metal cluster electroluminescent device based on a host-guest material system is obtained, wherein the evaporation rates of TPBi and LiF are 0.1 nm / s, and the evaporation rate of Al is 1 nm / s. Example 3
[0021] The following steps are involved: 1) Take 5 ml toluene containing Me2SAuCl (29.5 mg, 0.1 mmol), add 4-tBuPhC≡CH (18 μL, 0.1 mmol) and Et3N (40 μL), and stir for 5 minutes; 2) Add Cu(MeCN)4BF4 (12.6 mg, 0.04 mmol), and then quickly add 1 ml of freshly prepared BH3·tBuNH2 ethanol solution (1.7 mg). The reaction mixture is stirred at 20 °C in the dark for 4 hours. 3) The solvent obtained in 2) was rotary evaporated to obtain a solid, and the solid was dissolved in 2.0 ml of a 1:1 mixture of chromatographic grade dichloromethane and toluene, and centrifuged at 12000 r / min for 3 minutes; 4) Filter the precipitate in 3) and collect the filtrate, let it stand in a fume hood and use n-hexane diffusion crystallization to obtain dark red block crystals of Au after 96 hours. 16 Cu6; 5) dissolving the crystals obtained in 4) in chromatographically pure dichloromethane and adding powdered host material mCP and PO-T2T to the solution, stirring vigorously for 5 minutes to obtain a uniformly distributed host-guest mixed solution; 6) Spin coating the host-guest mixed solution in 5) onto the ITO glass substrate on which PEDOT:PSS has been spin-coated at a speed of 2000 rpm / s; comprising: First, the ITO conductive glass was cleaned with soap, deionized water, ethanol, chloroform, acetone and isopropanol in turn, and then treated with UV ozone. PEDOT: PSS solution (Baytron PVP Al 4083) was spin-coated on the treated ITO glass through a filter head at a speed of 2000 r / min, and then annealed at 170°C for 30 minutes to obtain a hole injection layer. The substrate was then transferred to a glove box filled with N2 gas. 7) The product obtained in 6) is finally transferred into a vacuum chamber, and TPBi, LiF and Al layers are sequentially deposited by thermal evaporation, wherein the TPBi layer serves as an electron transport layer and a hole blocking layer, and the LiF and Al layers serve as top electrodes; thus, a metal cluster electroluminescent device based on a host-guest material system is obtained, wherein the evaporation rates of TPBi and LiF are 0.1 nm / s, and the evaporation rate of Al is 1 nm / s.
[0022] like Figure 1 As shown in Figure 2, the synthesized crystals have the characteristic absorption and emission peaks of metal nanoclusters, ensuring the high purity of the material. Figure 2As shown in Figure 2, the transient photoluminescence spectrum shows that the cluster emitter has obvious thermally activated delayed fluorescence characteristics, which is conducive to the capture of electric excitons, laying the foundation for the manufacture of light-emitting diodes. Figure 3 As shown in Figure 2, the unoptimized metal cluster film has a high roughness, while the roughness of the metal cluster film optimized by the host-guest material system is significantly reduced. Figure 4 As shown in the figure, the semiconductor energy levels of the cluster emitter were determined, and the device structure was designed based on the measured values. Figure 5 As shown in the figure, LEDs were prepared with unoptimized metal clusters and metal nanoclusters optimized by the host-guest material system as the light-emitting layer, showing their optimized and unoptimized electroluminescence spectra. The smaller blue shift comes from the up-conversion characteristics of the host material, which changes the proportion of singlet and triplet excitons. Figure 6 , as shown in Figure 7, the optimized LED achieves 224cd / m 2 brightness and a peak external quantum efficiency of 0.176%.
Claims
1. A method for preparing a metal cluster-based infrared electroluminescent device, characterized in that: The following steps are involved: Step 1: Take 5 ml of toluene containing Me2SAuCl, add 4-tBuPhC≡CH and Et3N, and stir for 4-6 minutes; Step 2: Add Cu(MeCN)4BF4, then quickly add 1 ml of freshly prepared BH3·tBuNH2 in ethanol, and stir the reaction mixture in the dark at 20°C for 3.5-4.5 hours; Step 3: The solvent obtained in step 2 was rotary evaporated to obtain a solid, and the solid was dissolved in 2.0 ml of a 1:1 mixture of chromatographic grade dichloromethane and toluene, and centrifuged for 2-4 minutes; Step 4: Filter the precipitate in step 3 and collect the filtrate, let it stand in a fume hood and use n-hexane for diffusion crystallization. After 96 hours, dark red block crystals of Au are obtained. 16 Cu6; Step 5: dissolving the crystals obtained in step 4 in chromatographically pure dichloromethane and adding powdered host material mCP and PO-T2T to the solution, stirring vigorously for 4 to 6 minutes to obtain a uniformly distributed host-guest mixed solution; Step 6: Spin-coat the host-guest mixed solution in step 5 onto the ITO glass substrate on which PEDOT:PSS has been spin-coated to serve as a light-emitting layer; Step 7: The product obtained in step 6 is finally transferred into a vacuum chamber, and TPBi, LiF and Al layers are sequentially deposited by thermal evaporation, wherein the TPBi layer serves as an electron transport layer and a hole blocking layer, and the LiF and Al layers serve as top electrodes; thus, a metal cluster electroluminescent device based on a host-guest material system is obtained.
2. The method for preparing a metal cluster-based infrared electroluminescent device according to claim 1, characterized in that: In step 1, the mass of Me2SAuCl is 29.5 mg, and the volumes of the aqueous 4-tBuPhC≡CH and Et3N are 18 μL and 40 μL, respectively.
3. The method for preparing a metal cluster-based infrared electroluminescent device according to claim 1, characterized in that: The masses of Cu(MeCN)4BF4 and BH3·tBuNH2 described in step 2 are 12.6 mg and 1.7 mg, respectively.
4. The method for preparing a metal cluster-based infrared electroluminescent device according to claim 1, characterized in that: In step 3, the centrifugal speed is 11000~13000 r / min.
5. The method for preparing a metal cluster-based infrared electroluminescent device according to claim 1, characterized in that: In step 5, the Au 16 The masses of Cu6 and the main materials mCP and PO-T2T are 5.0 mg, 1.0 mg and 1.0 mg respectively.
6. The method for preparing a metal cluster-based infrared electroluminescent device according to claim 1, characterized in that: In step 6, the ITO conductive glass is first cleaned with soap, deionized water, ethanol, chloroform, acetone and isopropanol in sequence, and then treated with ultraviolet ozone; the PEDOT: PSS solution is spin-coated on the treated ITO glass through a filter head, and then annealed to obtain a hole injection layer; The substrate was then transferred into a glove box filled with N2 gas.
7. The method for preparing a metal cluster-based infrared electroluminescent device according to claim 6, characterized in that: The annealing treatment of PeDOT: PSS is specifically annealing at a temperature of 170° C. for 30 minutes.
8. The method for preparing a metal cluster-based infrared electroluminescent device according to claim 6, characterized in that: The rotation speed of the spin coating PeDOT:PSS is 1900-2100 r / min.
9. The method for preparing a metal cluster-based infrared electroluminescent device according to claim 1, characterized in that: In step 6, the host-guest mixed solution is spin-coated on the PeDOT: PSS layer at a rotation speed of 1900~2100r / min.
10. The method for preparing a metal cluster-based infrared electroluminescent device according to claim 1, characterized in that: In step 7, the evaporation rate of TPBi and LiF is 0.1 nm / s, and the evaporation rate of Al is 1 nm / s.